Pharmaceuticals: Management Safety of Circulation of Drugs - Kharytonova, Ganna (SSP Modern Pharmacy and Medicine, 2024)
The adoption and implementation of EU pharmaceutical directives and regulatory documents in Ukraine will significantly enhance the level of public health protection. Establishing a unified pharmaceutical market with EU countries will also improve the safety, quality, and accessibility of medications in Ukraine. To achieve these objectives, a comprehensive system for managing drug circulation safety has been proposed, with detailed functions and roles elaborated. Key components of this safety management system include robust monitoring mechanisms, stringent regulatory compliance measures, and effective communication channels among stakeholders. By implementing these measures, Ukraine can ensure that drugs are safe, effective, and of high quality, thereby fostering greater public trust in the healthcare system. Additionally, the integration of advanced technologies and best practices from EU countries can streamline drug approval processes, reduce counterfeit medications, and enhance pharmacovigilance. Efforts to improve the circulation of drugs will not only guarantee their safety and quality but also make them more readily available to the population. This will involve upgrading infrastructure, enhancing regulatory frameworks, and fostering collaboration with international pharmaceutical organizations. Overall, these initiatives are crucial for aligning Ukraine's pharmaceutical sector with European standards, ultimately leading to better health outcomes for its citizens and a more resilient healthcare system.